RETRACTED: Leap into Fetal Surgery; In Utero Placental Mesenchymal Stem Cell Therapy, A Contemporary Approach to Treating Myelomeningocele - Muhammad, Osama Siddiqui; Haya, Shahzad; Insa, Binte Anwar (Journal of Fetal Surgery, 2024)
This article has been retracted on April 10, 2025. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2997-2086.jfs-25-5857) Myelomeningocele (MMC), a class of spina bifida is a type of neural tube defect. According to the U.S. Centers for Disease Control and Prevention, each year approximately 1,400 babies born in the United States have spina bifida. The disease manifests with the lack of skin and bone covering the caudal part of the spinal cord. The patient developing such a condition often develops lifelong impaired lower limb mobility accompanied by hydrocephalus, and urinary and bowel incontinence. The available interventions include prenatal and postnatal surgery to fuse the dura. Prenatal surgery performed before 26 weeks of gestation reduces the risk of death or the need for ventriculoperitoneal shunting. It also enhanced results on a comprehensive index for mental and motor function. When compared to postnatal surgery, prenatal surgery reduces the manifestation of several secondary outcomes, including the degree of hindbrain herniation seen in the Chiari II malformation. Stem cell therapy for MMC on animal models of chick, ovine, and rodents with reported cases 15/63, 15, and 136, respectively, using human Embryonic Stem Cells (hESCs), Neural Stem Cells (NSCs), Mesenchymal Stem Cells (MSCs) showed significant coverage of MMC defect and slight neurogenesis was also observed. With an understanding of medical literature about in-utero regenerative capacity, it is to be appreciated that placental stem cells surgically seeded within a biocompatible scaffold of the cell patches can play a part in alleviating the spinal cord manifestation associated with MMC. Documented animal studies show that incorporating Placental Mesenchymal Stem Cells in prenatal surgery has reported improved neurogenesis and lower limb mobility. In an ovine myelomeningocele model, the development of in-utero myelomeningocele repair with human Placental Mesenchymal Stem Cells seeded onto an extracellular matrix (PMSC-ECM) enhances motor findings. The clinical trial for the first stem cell therapy on human subjects known as the “CuRe Trial: Cellular Therapy for In Utero Repair of Myelomeningocele.” is expected to be finished by 2030. So far, the cases undergoing treatment have shown significant leg movement and a greater degree of bowel and urinary control. This FDA-approved clinical trial is envisioned to be the future of treating MMC.
Keywords: Myelomeningocele; Placental Mesen chymal Stem Cells; prenatal surgery; stem cell therapy